2013
DOI: 10.1007/s00374-013-0853-z
|View full text |Cite
|
Sign up to set email alerts
|

Snow cover and soil moisture controls of freeze–thaw-related soil gas fluxes from a typical semi-arid grassland soil: a laboratory experiment

Abstract: In situ field measurements as well as targeted laboratory studies have shown that freeze-thaw cycles (FTCs) affect soil trace gas fluxes. However, most of past laboratory studies adjusted soil moisture before soil freezing, thereby neglecting that snow cover or water from melting snow may modify effects of FTCs on soil trace gas fluxes. In the present laboratory study with a typical semi-arid grassland soil, three different soil moisture levels (32 %, 41 %, and 50 % WFPS) were established (a) prior to soil fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
(101 reference statements)
3
29
0
Order By: Relevance
“…In general, alpine meadow soils in the Qinghai-Tibet Plateau are CH 4 sinks (Jiang et al 2010). After the frozen soils thawed, the rate at which the soils absorbed CH 4 increased quickly, consistent with previous studies (Dörsch et al 2004;Wu et al 2014). The increase in CH 4 uptake after thawing is primarily due to the fact that CH 4 , which diffuses from the atmosphere into the soils, was oxidized by the reactivated CH 4 -oxidizing bacteria, so that the negative emissions increased compared with those during freezing (Hütsch 1998).…”
Section: Discussionsupporting
confidence: 79%
“…In general, alpine meadow soils in the Qinghai-Tibet Plateau are CH 4 sinks (Jiang et al 2010). After the frozen soils thawed, the rate at which the soils absorbed CH 4 increased quickly, consistent with previous studies (Dörsch et al 2004;Wu et al 2014). The increase in CH 4 uptake after thawing is primarily due to the fact that CH 4 , which diffuses from the atmosphere into the soils, was oxidized by the reactivated CH 4 -oxidizing bacteria, so that the negative emissions increased compared with those during freezing (Hütsch 1998).…”
Section: Discussionsupporting
confidence: 79%
“…This could lead to inverted soil temperature patterns in winter, that is, to ‘colder soils in a warmer world’, due to reduced soil insulation of snowpack and to increased frequency of freeze–thaw cycles (Groffman et al ., ). Such freeze–thaw cycles have been shown to be biogeochemical key periods with, for example, pulses of nutrient leaching or emission of the potent greenhouse gas nitrous oxide (N 2 O) (Matzner & Borken, ; Wolf et al ., ; Wu et al ., ). Unteregelsbacher et al .…”
Section: Introductionmentioning
confidence: 97%
“…Wetting dry soil can stimulate atmospheric CH 4 oxidation in unsaturated upland soils mainly by alleviating osmotic stress on soil methanotrophs2324, but the effect of the availability of soil C and N upon wetting on soil CH 4 oxidation is not known. Wu et al 25. reported that there was a significant increase in the CH 4 uptake activity following thawing and this increase generally decreased by increasing soil moisture from 32 to 55% WFPS.…”
mentioning
confidence: 99%